Patients With Microscopic Colitis Have Altered Levels of Inhibitory and Stimulatory Biomarkers in Colon Biopsies and Sera Compared to Non-inflamed Controls - Lushnikova, Alexandra; Bohr, Johan; Wickbom, Anna; Münch, Andreas; Sjöberg, Klas; Hultgren, Olof; Wirén, Anders; Hultgren Hörnquist, Elisabeth (Frontiers in Medicine, 2021)
Introduction: Microscopic colitis (MC) is an inflammatory bowel condition with two subtypes, lymphocytic colitis (LC) and collagenous colitis (CC). Unlike patients with ulcerative colitis (UC) and non-inflamed individuals, MC patients have reduced risk of developing colorectal cancer, possibly due to increased immune surveillance in MC patients. Aim: To examine differences in levels of immunomodulatory molecules, including those involved in immune checkpoint mechanisms, in sera from patients with MC and in colonic biopsies from patients with MC and UC compared with controls. Methods: Using Luminex, 23 analytes (4-1BB, 4-1BBL, APRIL, BAFF, BTLA, CD27, CD28, CD80, CTLA-4, E-cadherin, Galectin-3, GITR, HVEM, IDO, IL-2Rα, LAG-3, MICA, MICB, PD-1, PD-L1, PD-L2, sCD40L and TIM-3) were studied in serum from patients with active MC (n = 35) and controls (n = 23), and in colonic biopsies from patients with active LC (n = 9), active CC (n = 16) and MC in histological remission (LC n = 6, CC n = 6), active UC (n = 15) and UC in remission (n = 12) and controls (n = 58). Results: In serum, IDO, PD-1, TIM-3, 4-1BB, CD27, and CD80 were decreased whereas 4-1BBL and IL-2Rα were increased in MC patients compared with controls. In contrast, in biopsies, levels of PD-L2 and 4-1BB were increased in MC and UC patients with active disease. Furthermore, in biopsies from CC and UC but not LC patients with active disease, CTLA-4, PD-1, APRIL, BAFF, and IL-2Rα were increased compared with controls. PD-L1 was increased in CC but not UC or LC patients. CD27 and TIM-3 were decreased in biopsies from MC patients in comparison to controls whereas levels of MICB were decreased in patients with active UC compared with controls. Conclusions: Compared with non-inflamed controls, levels of soluble and membrane-bound immunomodulatory molecules were systemically and locally altered in MC and UC patients, with most analytes being decreased in serum but enhanced in colonic biopsies. These findings contribute to knowledge about checkpoint molecules and their role as biomarkers in MC and may also contribute to knowledge about possible mechanisms behind the seemingly protective effects of MC against colorectal cancer.